Exploring Early Childhood Independence in Relation to Mother's Employment Status - Mayasari; Yusnadi; Muhammad Takwin Machmud (International Journal of Educational Practice and Policy, 2023)
This study aims to determine differences in early childhood independence based on the mother's employment status in Madrasah Diniyah Awwaliyah (MDA) Kampung Durian, Medan Perjuangan District. The method used in this study is a qualitative method with descriptive qualitative data analysis, in which the data collected are in the form of words and pictures rather than numbers. The data used in this research are primary data obtained directly from the field through observation and interviews. The results of this study show that students who have employed mothers demonstrate a higher level of independence compared to students whose mothers do not work, and the employment status of mothers can also be a factor influencing a child's independence.